ПРОБЛЕМА ВИКЛАДАННЯ ЛАТИНСЬКОЇ МОВИ НА ФАКУЛЬТЕТАХ ФІЛОЛОГІЇ У ВИЩІЙ ШКОЛІ - Паладьєва, Алла (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті розглядається проблема вивчення латинської мова на філологічних факультетах у вищих навчальних закладах освіти як фахової дисципліни. Визначено необхідність вивчення і переосмислення досвіду минулого, який забезпечує дотримання принципів єдності, системності та наступності в розвитку педагогічної науки загалом і питань змісту освіти зокрема. Розглянуто завдання, які ставляться перед студентами у процесі вивчення ними латинської мови на заняттях та позанавчальний час. В статье рассматривается проблема изучения латинского языка на филологических факультетах в высших учебных заведениях как специальной дисциплины. Определена необходимость изучения и переосмысление опыта прошлого, который обеспечивает соблюдение принципов единства, системности и преемственности в развитии педагогической науки в целом и по содержанию образования в частности. Рассмотрены задачи, которые ставятся перед студентами в процессе изучения ими латинского языка на занятиях и внеурочное время. The article deals with the problem of the study of the Latin language at the faculties of philology of higher educational institutions as a special discipline. The necessity of learning and rethinking past experience, which ensures compliance with the principles of unity, consistency and continuity in the development of science teaching in general and on educational content in particular was defined. The problems, which put forward the students during their study of Latin in the classroom and outside it were enlighten . Latin is the language of communicative nature has certain limitations in forming speech and linguistic competence: speech is realized at only reading and writing, linguistic – knowledge at pronouncing, spelling, vocabulary and grammar rules, basic language laws and rules of construction terms. The principle of originality and authenticity of the material - it meant living at teaching foreign languages - can not be implemented fully in learning Latin. Basically, the emphasis on authenticity is designed; the terminology should be adequate to modern terminology and nomenclature codes.